Analisis Kemampuan Pemecahan Masalah dalam Menyelesaikan Soal Cerita pada Materi Operasi Hitung Campuran Kelas II Sekolah Dasar - Dewi Budi Juniati; Ryky Mandar Sary; Filia Prima Artharina (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study was to describe the problem-solving ability in solving math's word problems on mixed arithmetic operations in grade 2 of elementary school level. This research used a qualitative descriptive approach. The subject of this study consisted of 22 students, then 6 students were taken to be interviewed with the criteria: 2 high abilities; 2 moderate abilities; and 2 low abilities. In this study, researchers also used several methods to collect data: tests, interviews, and documentation. The validity test was done by using the triangulation technique. The result of this research was analyzed using Polya's problem-solving indicator with a percentage of 55.98% in the "fair" category. These are the following details: (1) The problem understanding indicator with a percentage of 79.39% for the "good" category.  (2) The indicator of problem-solving planning with a percentage of 74.54% for the "good" category. (3) The carry out problem-solving indicator with a percentage of 45.45% for the "fair" category. (4) The look back of problem-solving indicator with a percentage of 24.54% for the “poor” category.